Entre sclérose et renouveau - Éric Suire (Mélanges de la Casa de Velázquez)
French Renaissance hagiography is an extension of mediaeval tradition. The saints of the New Testament and of early Christianity remained the models of reference; however, the Golden Legend, despite its undoubted aura, came under heavy criticism from Reformists. In the 1540s, several printers went over to Calvinism, and the production of the Lives of Saints came to a standstill. However, around 1580 there came the first signs of a timid renewal, as the influence of the Catholic League propagated dissemination of the spiritual biographies of the heralds of the Catholic Reformation, brought in from Italy and Spain. Traditionally the domain of the Dominicans, the role of hagiographers passed on to Jesuit writers in response to changing tastes, reflected in growing enthusiasm for more recent personalities and the Lives of mystics.